IMPLEMENTATION OF INFERENCE ENGINE WITH CERTAINTY FACTOR ON POTENTIAL DIAGNOSIS OF BRAIN TUMOR DISEASE - Harjanti, Trinugi Wira (Jurnal Pilar Nusa Mandiri, 2022)
An expert system is a system that has the ability of experts or experts who master a particular field to assist in solving problems. Certainty factor (CF) is one of the methods in an expert system that can define the level of certainty based on facts to show the level of confidence of the expert. This study aims to apply a certainty factor (CF) algorithm to solve the problem of diagnosing potential human brain tumors. Because the symptoms that are felt are not necessarily brain tumors, it is necessary to analyze whether the person has the potential to have a brain tumor or not, even if the potential level is. Brain tumor disease is one of several types of dangerous conditions. This disease is caused by the abnormal growth of cells around the brain. This research produces an application that can diagnose potential brain tumor diseases based on symptom input selected by the user. Then the expert system can display the diagnosis results in percentages and solutions from the results of the diagnosis. The study results indicate that the CF method can solve the problem of uncertainty by giving a degree of confidence from an expert and system user. The accuracy test results resulted in an accuracy value reaching 95%. These results indicate that the system can function and can diagnose potential brain tumor diseases properly